Aktivitas Antidiabetes Ektrak Etanol Pelepeh Nipah (Nypa fruticans. Wurmb) Terhadap Tikus Model Diabetes - Danang Raharjo; M. Adam Firdausi; Bangkit Riska P (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Diabetes Mellitus remains a global health challenge. In Indonesia, diabetes ranks as the third leading cause of death, after heart disease and cancer. Flavonoids, as natural antioxidants, have proven effective in mitigating the pathogenesis and complications of diabetes. Nypa fruticans is a plant with potential as an antidiabetic agent due to its high flavonoid content.This study aimed to measure the total flavonoid content and explore the potential of ethanol extract of nipa fronds as an antidiabetic, specifically in reducing blood glucose levels. Flavonoid content was determined using the AlCl₃ complex method. Antidiabetic testing was conducted in-vivo using STZ-induced diabetic rat model. Ethanol extracts of nipa fronds at doses of 125, 250, and 500 mg/kg were administered to STZ (65 mg/kg)-induced diabetic rats for 21 days, with glibenclamide (0.45 mg/kg) serving as a positive control.The study results show that the ethanol extract of nipa fronds has a total flavonoid content of 48.247 ± 0.260 mgQE/g. In the antidiabetic testing, the ethanol extract of nipa fronds at a dose of 500 mg/kg BW significantly reduced the blood glucose levels of diabetic rats compared to the negative control (p<0.05) and was comparable to the positive control. Therefore, it can be concluded that the ethanol extract of nipa fronds can be utilized for managing Type 2 Diabetes Mellitus.